RETRACTED: The role of human capital and effective innovations for the economic growth of the country - Merkulova E.Yu.; Sysoeva M.S.; Mahonina I.N. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001